Enhancing the flexural behavior of brick masonry walls with ferrocement overlays and low-cost anchors - Saingam, Panumas; Hlaing, Hnin Hnin; Suwannatrai, Rawirot; Ejaz, Ali; Hussain, Qudeer; Khan, Kaffayatullah; Joyklad, Panuwat (My University, 2023)
This study presents an innovative approach to enhance the flexural capacity of cement-clay interlocking (CCI) brick walls using ferrocement jackets with an expanded wire mesh. The investigation involved 15 CCI brick walls subjected to flexural load testing, exploring various mesh sizes and anchor configurations on single and dual sides. The results revealed that while the primary failure mode involved dry joint opening and subsequent ferrocement debonding in the strengthened walls, effective anchorage mechanisms delayed dry joint opening until debonding occurred. The reinforced walls exhibited improved peak load capacity, notably in dual-sided reinforcement cases. With plastering on both sides and supplemented with anchors, an improvement of up to 221% in flexural capacity was obtained. The study emphasizes the influence of wire mesh size on anchorage effectiveness and its correlation with debonding susceptibility. Additionally, the moment-curvature analysis demonstrated resilient, ductile responses in load-bearing characteristics, with occasional abrupt declines due to ferrocement jacket debonding. Unlike control walls, the strengthened walls exhibited strains exceeding yield thresholds, indicating enhanced structural performance.
Keywords: Cement-clay interlocking bricks; Dry joint opening; Expanded wire mesh; Ferrocement; Masonry walls; Moment-curvature